Wound healing ability of white type edible jellyfish Lobonema smithii in white rats - Suvik Assaw (Fakulti Pengajian Maritim dan Sains Marin, 2011)
White type edible jellyfish, Lobonema smithii were desalted, dried and extracted to formulate for oral consumption in white rats in wound healing study. Prior to that it was subjected to toxicity screening and tested for antioxidant activity. Methanolic and cold acetone protein precipitation extraction method was done to obtain methanol crude extract and crude protein extract.